Impact of Domestic Institutional Investors on Indian Stock Market - SALAR, S.A. Atif (Journal of Advanced Studies in Finance, 2017)
Indian stock market used to see investments from two major types of Institutional Investors. One is Domestic Institutional Investors and other is Foreign Institution Investors. There have been many studies on Foreign Institutional Investors but none of the study focuses on the role Domestic Institutional Investors used to play in Indian Stock Market. This paper tries to examine the relationship between Domestic Institutional Investors and India stock market (SENSEX). The causality between the investments made by Domestic Institutional Investors and movement of Sensex has been analyzed using Granger causality test. The data from 2009 to 2016 has been analyzed by taking the net investments made by DIIs and closing value of Sensex index. Various econometric tools have been used to establish the causal relationship between Domestic Institutional Investor flows and Sensex return. The analysis includes Vector Auto Regression (VAR) and Granger causality which shows that DIIs does not have any positive influence on Sensex return but the vice-versa i.e. the movement of sensex definitely makes an impact of the investment strategies of DIIs. The reason behind that is that the DIIs are not influencing the Indian Stock market but rather Foreign Institutional Investors might play an important role in influencing the Sensex. Other than VAR, impulse response and Variance Decomposition have also been used to give more strength to the results.
Keywords: domestic institutional investors; Granger causality; Sensex; VAR